Дослідження давньоруського Любомля - Златогорський, О.Є.; Панишко, С.Д. (Археологічні дослідження в Україні, 2009)
The paper presents the main results of the research at Ancient Rus Lyboml in the 2008 season. The most interesting is a partly excavated log cabin and individual finds, namely, a big pointed amulet made of a horn. The research resu